Hasil Belajar PAI Siswa Kelas VIII.3 Di SMPN 2 X Koto Kecamatan X Koto Kabupaten Tanah Datar - Reni Nofriza; Iswantir Iswantir; Salmi Wati; Arifmiboy Arifmiboy; Bobi Iskandar (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
This type of research is field research (Field Research) using a qualitative descriptive method to obtain the data studied. The data collection technique used is through interviews and documentation. The research data sources are primary data sources and secondary data sources. Data validity assurance techniques used is Triangulation. The data analysis technique used is data analysis technique, namely data reduction, data display, and data verification. Based on student learning outcomes, it has not been achieved well. Judging from the data or student scores, it ranges from 75-79 with sufficient predicate, only a few students achieve 80-90, and from the data obtained by the school, 19 out of 33 students achieve sufficient predicate scores. with the average has not been reached to the maximum. Even then, the value of the learning outcomes has been assisted by carrying out remedial or repeat exams when student scores are problematic and assisted with plus values from the student's personality, therefore the authors conclude that PAI learning has not achieved maximum learning goals, so it needs stages or performance. maximum to improve learning outcomes so that learning is achieved properly. Then in terms of effective learning, some students have problems with interest or interest in PAI learning, therefore it has an impact on learning outcomes that are not achieved properly, and also has an impact on a child's attitude or behavior that is not good, such as behavior in daily life, such as every worship Zuhur students must be guided to carry out the worship not their own desires, then from a psychomotor point of view the children are still not well achieved that in the learning process there are some students with problem-solving skills such as not being active in discussions, not being fluent in reading Alqur'an skills and writing verses The Koran is blackboard.